Differential outcomes in an extended family with constitutional t(11;22)(q23.3;q11.2) - Kee, Su Keyau; See, Valene Hsu-Lin; Chia, Patrick; Tan, Wei Ching; Tien, Sim Leng; Lim, Soon Tiong Alvin (Journal of Pediatric Genetics, 2013)
The t(11;22) rearrangement is the most common recurrent familial reciprocal translocation in man. Heterozygote carriers are phenotypically normal but are at risk of subfertility in the male, miscarriages, and producing chromosomally unbalanced offspring. The unbalanced progeny usually results from an extra der(22) chromosome resulting from a 3:1 malsegregation. We present here a family with t(11;22). Of six siblings, three were found to be carriers following prenatal diagnosis of the proband fetus. Neither of the two married carrier siblings have a live born child. In keeping with the prevailing knowledge of the pregnancy outcomes of heterozygote carriers, between the siblings they had recurrent miscarriages, a fetus with a +der(22) chromosome, and other subfertility issues resulting in multiple failed in vitro fertilization cycles with preimplantation genetic diagnosis. However, unlike the siblings, their extended family comprising their heterozygote translocation mother, married aunts and an uncle had normal fertility and a lack of a history of miscarriages or an abnormal child. The differing outcomes may be related to the male partners having additional semen anomalies which may further exacerbate problems associated with the t(11;22). Because the t(11;22) rearrangement tends to run in families, it is recommended that chromosome studies are offered to family members of an affected relative as an option, and provide them with appropriate genetic counseling so that they will have the necessary information with regard to their risk for subfertility, miscarriages, and production of viable unbalanced offspring. Follow-up prenatal diagnosis should also be offered to affected expectant family members, especially after preimplantation genetic diagnosis.
Keywords: Emanuel syndrome; subfertility; miscarriage; preimplantation genetic diagnosis; +der(22)t(11; 22) syndrome